Nonaqueous electrolyte and nonaqueous secondary battery
By using a specific proportion of acetonitrile solvents, lithium salts and sulfite compound additives in the non-aqueous electrolyte, the performance attenuation problem of nonaqueous secondary batteries in high temperature environments is solved, and the stable output and wide application of the battery at high temperatures is achieved.
Patent Information
- Application Number
- JP2021053801
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2041-03-26
AI Technical Summary
The existing nonaqueous secondary batteries using acetonitrile as solvent have reduced performance in high temperature environments and insufficient output performance, which fail to meet the long-term use requirements.
A non-aqueous solvent containing 5% to 95% acetonitrile is used, combined with lithium bisfluorosulfonimide and LiPF6 as the lithium salt, and 1% to 5% sulfite compound as the additive, forming a specific concentration of nonaqueous electrolyte to improve the performance of the battery in high temperature environment.
Effectively maintain the output performance of the battery in high temperature environments, improve the application capability of the battery in a wide range, and reduce performance attenuation.
Smart Images

Figure 0007628451000007 
Figure 0007628451000008 
Figure 0007628451000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a nonaqueous electrolyte and a nonaqueous secondary battery. [Background technology]
[0002] Non-aqueous secondary batteries containing non-aqueous electrolyte solutions are characterized by their light weight, high energy and long life, and are widely used as power sources for portable electronic devices such as notebook computers, mobile phones, digital cameras, video cameras, etc. In addition, with the transition to a society with a low environmental impact, non-aqueous secondary batteries are attracting attention as power sources for hybrid electric vehicles (hereinafter abbreviated as "HEVs") and plug-in HEVs (hereinafter abbreviated as "PHEVs"), as well as in the field of power storage such as residential power storage systems.
[0003] When non-aqueous secondary batteries are installed in vehicles such as automobiles and residential power storage systems, from the viewpoint of cycle performance and long-term reliability in high-temperature environments, the constituent materials of the batteries are required to have excellent chemical and electrochemical stability, strength, corrosion resistance, etc. Furthermore, non-aqueous secondary batteries for vehicles such as automobiles and residential power storage systems have significantly different usage conditions from those of portable electronic device power sources and must also operate in cold regions, so high output performance and long life performance in low-temperature environments are also required as necessary physical properties.
[0004] In the above-mentioned situation, in order to realize a non-aqueous secondary battery having output performance, a nitrile-based solvent with an excellent balance between viscosity and dielectric constant has been proposed as a non-aqueous solvent. Among them, acetonitrile is known to be a solvent with outstanding performance, but these solvents containing nitrile groups have a fatal drawback of electrochemically undergoing reductive decomposition, and therefore several measures for improving the same have been reported. For example, the following Patent Documents 1 and 2 report an electrolyte solution in which the influence of reductive decomposition of acetonitrile is reduced by combining the solvent acetonitrile with a specific electrolyte salt, additive, etc., and as a particularly suitable example, a sulfite ester compound is used as an additive.
[0005] Furthermore, Patent Document 3 reports, as a good example, a system in which acetonitrile is used as a solvent and an imide salt such as lithium bis(fluorosulfonyl)imide is combined with a fluorine-containing inorganic lithium salt as an electrolyte salt.
[0006] Incidentally, with regard to a sulfite ester compound represented by ethylene sulfite, Patent Document 4 proposes using one in which the concentration of free acid HSO contained as an impurity is adjusted as low as possible in order to contribute to further improving the performance of an electricity storage device. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2012 / 057311 [Patent Document 2] International Publication No. 2013 / 062056 [Patent Document 3] JP 2015-65049 A [Patent Document 4] JP 2010-120947 A Summary of the Invention [Problem to be solved by the invention]
[0008] Secondary batteries that use acetonitrile as a solvent for a non-aqueous electrolyte solution have an issue of performance degradation when placed in a high-temperature environment for a long period of time. The issue has not yet been fully resolved, and the output performance of the batteries cannot be fully utilized.
[0009] The present invention has been made in consideration of the above circumstances, and therefore an object of the present invention is to provide a nonaqueous secondary battery that uses an acetonitrile-containing nonaqueous electrolyte solution and that is less susceptible to performance degradation even in a high-temperature environment. [Means for solving the problem]
[0010] The present inventors have conducted extensive research to solve the above-mentioned problems, and as a result, have found that the above-mentioned problems can be solved by using a nonaqueous electrolyte solution or a nonaqueous secondary battery having the following configuration, thereby completing the present invention. <1> A non-aqueous electrolyte solution containing a non-aqueous solvent and a lithium salt, wherein the non-aqueous solvent contains 5% by volume or more and 95% by volume or less of acetonitrile based on a total amount of the non-aqueous solvent, and the lithium salt contains lithium bisfluorosulfonylimide and LiPF6, and a compound represented by the following general formula (I): [ka] In the formula, R1 and R2 are each an alkyl group having 1 to 4 carbon atoms in which a hydrogen atom may be substituted with a fluorine atom, or R1 and R2 may be bonded to form a ring. The nonaqueous electrolyte contains a sulfite ester compound represented by the formula: 2- The non-aqueous electrolyte solution has a content of 10 ppm or more and 500 ppm or less. <2> 2. The nonaqueous electrolyte solution according to item 1, wherein the sulfite compound is ethylene sulfite. <3> 3. The non-aqueous electrolyte solution according to claim 1 or 2, wherein the non-aqueous solvent comprises a cyclic carbonate. <4> 4. The nonaqueous electrolyte solution according to item 3, wherein the cyclic carbonate comprises at least one selected from the group consisting of vinylene carbonate and fluoroethylene carbonate. <5> 5. A nonaqueous secondary battery comprising: the nonaqueous electrolyte according to any one of items 1 to 4; a positive electrode having a positive electrode active material layer on one or both sides of a positive electrode current collector; a negative electrode having a negative electrode active material layer on one or both sides of a negative electrode current collector; and a separator. <6> the positive electrode active material layer contains a lithium-containing metal oxide as a positive electrode active material, The negative electrode active material layer contains lithium ions as a negative electrode active material at 0.4 V vs. Li / Li + 6. The nonaqueous secondary battery according to item 5, further comprising a material capable of occluding at a potential lower than 0.1 V. Effect of the Invention
[0011] According to the present invention, a sulfite ester compound and SO4 are mixed in a non-aqueous electrolyte at a specific concentration. 2- By containing the above, it is possible to provide a nonaqueous secondary battery which can be used in a wider range of applications, since deterioration of battery characteristics under high temperature environments is improved while maintaining output performance. [Brief description of the drawings]
[0012] [Figure 1] 1 is a plan view illustrating a schematic example of a nonaqueous secondary battery according to an embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view taken along line AA of the nonaqueous secondary battery of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The present invention is not limited to the following embodiment, and various modifications are possible without departing from the gist of the present invention. In this specification, a numerical range described using "~" includes the numerical values described before and after it.
[0014] <Non-aqueous secondary battery> The nonaqueous electrolyte of the present embodiment can be used in a nonaqueous secondary battery. There are no particular limitations on the negative electrode, positive electrode, separator, and battery exterior of the nonaqueous secondary battery of the present embodiment.
[0015] Furthermore, although not limited thereto, examples of the nonaqueous secondary battery of the present embodiment include lithium ion batteries including a positive electrode containing, as a positive electrode active material, a positive electrode material capable of absorbing and releasing lithium ions, and a negative electrode containing, as a negative electrode active material, a negative electrode material capable of absorbing and releasing lithium ions and / or metallic lithium.
[0016] Specifically, the nonaqueous secondary battery of this embodiment may be the nonaqueous secondary battery shown in Figures 1 and 2. Here, Figure 1 is a plan view that shows a schematic diagram of the nonaqueous secondary battery, and Figure 2 is a cross-sectional view taken along line AA in Figure 1.
[0017] The nonaqueous secondary battery 100 shown in FIG. 1 and FIG. 2 is composed of a pouch-type cell. The nonaqueous secondary battery 100 contains a laminated electrode body formed by laminating a positive electrode 150 and a negative electrode 160 with a separator 170 interposed therebetween, and a nonaqueous electrolyte (not shown) in a space 120 of a battery exterior 110 formed of two aluminum laminate films. The battery exterior 110 is sealed at its outer periphery by heat-sealing the upper and lower aluminum laminate films. The laminate formed by laminating the positive electrode 150, the separator 170, and the negative electrode 160 in this order is impregnated with a nonaqueous electrolyte. However, in FIG. 2, in order to avoid the drawing becoming complicated, the layers constituting the battery exterior 110 and the layers of the positive electrode 150 and the negative electrode 160 are not shown separately.
[0018] The aluminum laminate film constituting the battery exterior 110 is preferably made of aluminum foil coated on both sides with a polyolefin resin.
[0019] The positive electrode 150 is connected to the positive electrode lead body 130 within the nonaqueous secondary battery 100. Although not shown, the negative electrode 160 is also connected to the negative electrode lead body 140 within the nonaqueous secondary battery 100. One end of each of the positive electrode lead body 130 and the negative electrode lead body 140 is drawn out to the outside of the battery exterior 110 so that they can be connected to an external device, and the ionomer portions of these are heat-fused to one side of the battery exterior 110.
[0020] 1 and 2, the positive electrode 150 and the negative electrode 160 each have one laminated electrode body, but the number of laminated positive electrodes 150 and negative electrodes 160 can be appropriately increased depending on the capacity design. In the case of a laminated electrode body having a plurality of positive electrodes 150 and negative electrodes 160, the tabs of the same electrode may be joined by welding or the like and then joined to a single lead body by welding or the like and taken out of the battery. The tabs of the same electrode may be formed from an exposed portion of a current collector, or may be formed by welding a metal piece to an exposed portion of a current collector.
[0021] The positive electrode 150 is composed of a positive electrode active material layer made of a positive electrode mixture and a positive electrode current collector. The negative electrode 160 is composed of a negative electrode active material layer made of a negative electrode mixture and a negative electrode current collector. The positive electrode 150 and the negative electrode 160 are arranged with the separator 170 between them so that the positive electrode active material layer and the negative electrode active material layer face each other.
[0022] As these components, materials that are used in conventional lithium ion batteries can be used as long as they satisfy the requirements of this embodiment. Each component of the nonaqueous secondary battery will be described in more detail below.
[0023] <Positive electrode> The positive electrode 150 is composed of a positive electrode active material layer made of a positive electrode mixture and a positive electrode current collector. The positive electrode 150 is not particularly limited as long as it acts as a positive electrode of a nonaqueous secondary battery, and may be a known one.
[0024] The positive electrode active material layer preferably contains a positive electrode active material, and further contains a conductive assistant and a binder as required.
[0025] The positive electrode active material layer preferably contains, as the positive electrode active material, a material capable of occluding and releasing lithium ions. When such a material is used, it is preferable because a high voltage and a high energy density can tend to be obtained.
[0026] Examples of the positive electrode active material include a positive electrode active material containing at least one transition metal element selected from the group consisting of Ni, Mn, and Co, and the lithium-containing metal oxide is, for example, represented by the following general formula (a): Li p Ni q Co r Mn s M t O u ·····(a) {In the formula, M is at least one metal selected from the group consisting of Al, Sn, In, Fe, V, Cu, Mg, Ti, Zn, Mo, Zr, Sr, and Ba, and 0 < p < 1.3, 0 < q < 1.2, 0 < r < 1.2, 0 ≦ s < 0.5, 0 ≦ t < 0.3, 0.7 ≦ q + r + s + t ≦ 1.2, 1.8 < u < 2.2, and p is a value determined by the charge and discharge state of the battery} At least one selected from lithium (Li)-containing metal oxides represented by the formula is preferable.
[0027] Specific examples of the positive electrode active material include, for example, lithium cobalt oxide typified by LiCoO2; lithium manganese oxide typified by LiMnO2, LiMn2O4, and Li2Mn2O4; lithium nickel oxide typified by LiNiO2; LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.2 O2 typified by Li zMO₂ {wherein M contains at least one transition metal element selected from the group consisting of Ni, Mn, and Co, and represents two or more metal elements selected from the group consisting of Ni, Mn, Co, Al, and Mg, and z represents a number greater than 0.9 and less than 1.2}, and lithium-containing composite metal oxides represented thereby can be mentioned.
[0028] In particular, when the Ni content ratio q of the Li-containing metal oxide represented by the general formula (a) is 0.5 < q < 1.2, it is preferable because both the reduction of the usage amount of Co, which is a rare metal, and the increase in the energy density can be achieved. As such a positive electrode active material, for example, LiNi 0.6 Co 0.2 Mn 0.2 O₂, LiNi 0.75 Co 0.15 Mn 0.15 O₂, LiNi 0.8 Co 0.1 Mn 0.1 O₂, LiNi 0.85 Co 0.075 Mn 0.075 O₂, LiNi 0.8 Co 0.15 Al 0.05 O₂, LiNi 0.81 Co 0.1 Al 0.09 O₂, LiNi 0.85 Co 0.1 Al 0.05 O₂, etc., and lithium-containing composite metal oxides represented thereby can be mentioned.
[0029] On the other hand, as the Ni content ratio increases, the deterioration tends to progress at a low voltage. In the positive electrode active material of the Li-containing metal oxide represented by the general formula (a), active points that oxidatively deteriorate the non-aqueous electrolyte essentially exist, but these active points may consume the compound added to protect the negative electrode unintentionally on the positive electrode side. Among them, acid anhydrides tend to be easily affected. In particular, when acetonitrile is contained as the non-aqueous solvent, the addition effect of the acid anhydride is extremely large, so the consumption of the acid anhydride on the positive electrode side is a fatal problem.
[0030] In addition, the decomposition products of these additives that are taken in and deposited on the positive electrode side not only increase the internal resistance of the non-aqueous secondary battery, but also accelerate the deterioration of the lithium salt, and furthermore, the protection of the negative electrode surface, which was the original purpose, becomes insufficient. In order to deactivate the active sites that essentially cause the oxidation deterioration of the non-aqueous electrolyte, it is important to control the Jahn-Teller distortion or to coexist with a component that plays a role as a neutralizer. Therefore, it is preferable that the positive electrode active material contains at least one metal selected from the group consisting of Al, Sn, In, Fe, V, Cu, Mg, Ti, Zn, Mo, Zr, Sr, and Ba.
[0031] For the same reason, the surface of the positive electrode active material is preferably coated with a compound containing at least one metal element selected from the group consisting of Zr, Ti, Al, and Nb. Also, the surface of the positive electrode active material is more preferably coated with an oxide containing at least one metal element selected from the group consisting of Zr, Ti, Al, and Nb. Furthermore, it is particularly preferable that the surface of the positive electrode active material is coated with at least one oxide selected from the group consisting of ZrO2, TiO2, Al2O3, NbO3, and LiNbO2, since this does not inhibit the permeation of lithium ions.
[0032] The positive electrode active material may be a lithium-containing compound other than the Li-containing metal oxide represented by the general formula (a), and is not particularly limited as long as it contains lithium. Examples of such lithium-containing compounds include composite oxides containing lithium and transition metal elements, metal chalcogenides containing lithium, metal phosphate compounds containing lithium and transition metal elements, and metal silicate compounds containing lithium and transition metal elements. From the viewpoint of obtaining a higher voltage, the lithium-containing compound is preferably a metal phosphate compound containing lithium and at least one transition metal element selected from the group consisting of Co, Ni, Mn, Fe, Cu, Zn, Cr, V, and Ti.
[0033] More specifically, the lithium-containing compound is represented by the following formula (Xa): Li v M I D2(Xa) In the formula, D represents a chalcogen element, and M I represents one or more transition metal elements, and the value of v is determined depending on the charge / discharge state of the battery and represents a number from 0.05 to 1.10. The following formula (Xb): Li w M II PO4(Xb) {In formula, M II represents one or more transition metal elements, and the value of w is determined depending on the charge / discharge state of the battery and represents a number from 0.05 to 1.10.}, and The following formula (Xc): Li t M III u SiO4(Xc) {In formula, M III represents one or more transition metal elements, the value of t is determined depending on the charge / discharge state of the battery and represents a number from 0.05 to 1.10, and u represents a number from 0 to 2. Examples of the compounds include those represented by the following formula:
[0034] The lithium-containing compound represented by the above formula (Xa) has a layered structure, and the compounds represented by the above formulas (Xb) and (Xc) have an olivine structure. These lithium-containing compounds may be those in which a part of the transition metal element is replaced by Al, Mg, or other transition metal element, those in which these metal elements are included in the crystal grain boundary, those in which a part of the oxygen atoms is replaced by fluorine atoms, etc., and those in which at least a part of the surface of the positive electrode active material is coated with another positive electrode active material, etc., for the purpose of stabilizing the structure.
[0035] In this embodiment, the positive electrode is a positive electrode active material represented by formula (Xb) having an olivine structure. xPreferably includes a lithium-containing metal oxide represented by FePO4, where 0 < x < 1.2, and more preferably is lithium iron phosphate (LiFePO4). The olivine-type structure has excellent thermal stability, a stable crystal structure, and a small primary particle size. Therefore, when the positive electrode active material contains a lithium-containing metal oxide having the olivine-type structure, the high-temperature durability tends to improve. The above Li x The content of the compound represented by FePO4 is preferably 40% by mass to 100% by mass, more preferably 60% by mass to 100% by mass, and still more preferably 80% by mass to 100% by mass based on the total mass of the positive electrode active material. The positive electrode active material may be Li x FePO4 may be used alone or may contain other positive electrode active materials.
[0036] As the positive electrode active material in this embodiment, only the above lithium-containing compound may be used, or other positive electrode active materials may be used in combination with the lithium-containing compound.
[0037] Examples of other positive electrode active materials include metal oxides or metal chalcogenides having a tunnel structure and a layered structure; sulfur; conductive polymers, etc. Examples of metal oxides or metal chalcogenides having a tunnel structure and a layered structure include metal oxides, sulfides, selenides, etc. of metals other than lithium represented by MnO2, FeO2, FeS2, V2O5, V6O 13 , TiO2, TiS2, MoS2, and NbSe2. Examples of conductive polymers include conductive polymers represented by polyaniline, polythiophene, polyacetylene, and polypyrrole.
[0038] The above-mentioned other positive electrode active materials are used alone or in combination of two or more, and there is no particular limitation. However, since it is possible to reversibly and stably occlude and release lithium ions and achieve a high energy density, it is preferable that the positive electrode active material layer contains at least one transition metal element selected from Ni, Mn, and Co.
[0039] When a lithium-containing compound and another positive electrode active material are used in combination as the positive electrode active material, the ratio of the two is preferably 80 mass % or more, and more preferably 85 mass % or more, of the lithium-containing compound relative to the total positive electrode active material.
[0040] Examples of the conductive additive include carbon black, such as graphite, acetylene black, and ketjen black, and carbon fiber. The content of the conductive additive is preferably 10 parts by mass or less, and more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the positive electrode active material.
[0041] Examples of the binder include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid, styrene butadiene rubber, and fluororubber. The content of the binder is preferably 6 parts by mass or less, and more preferably 0.5 to 4 parts by mass, relative to 100 parts by mass of the positive electrode active material.
[0042] The positive electrode active material layer is formed by dispersing a positive electrode mixture, which is a mixture of a positive electrode active material and, if necessary, a conductive assistant and a binder, in a solvent to form a positive electrode mixture-containing slurry, applying the slurry to a positive electrode current collector, drying (solvent removal), and pressing as necessary. There is no particular restriction on such a solvent, and a conventionally known solvent can be used. Examples of the solvent include N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, and water.
[0043] The positive electrode current collector is composed of a metal foil such as aluminum foil, nickel foil, stainless steel foil, etc. The positive electrode current collector may have a carbon coating on the surface, or may be processed into a mesh shape. The thickness of the positive electrode current collector is preferably 5 to 40 μm, more preferably 7 to 35 μm, and even more preferably 9 to 30 μm. In the case of a mesh-shaped positive electrode current collector, the thickness may be measured at a non-perforated portion.
[0044] <Negative electrode> The negative electrode 160 is composed of a negative electrode active material layer made of a negative electrode mixture and a negative electrode current collector. The negative electrode 160 can function as a negative electrode of a non-aqueous secondary battery.
[0045] The negative electrode active material layer contains a negative electrode active material, and preferably contains a conductive assistant and a binder as necessary.
[0046] Examples of the negative electrode active material include amorphous carbon (hard carbon), graphite (e.g., artificial graphite, natural graphite, etc.), pyrolytic carbon, coke, glassy carbon, baked bodies of organic polymer compounds, mesocarbon microbeads, carbon fibers, activated carbon, carbon colloids, and carbon black, as well as metal lithium, metal oxides, metal nitrides, lithium alloys, tin alloys, silicon alloys, intermetallic compounds, organic compounds, inorganic compounds, metal complexes, organic polymer compounds, etc. The negative electrode active material may be used alone or in combination of two or more.
[0047] The negative electrode active material layer is made of lithium ions at 0.4V vs. Li / Li in order to increase the battery voltage. + It is preferable that the hydrogen-containing gas contains a material capable of occluding at a potential lower than the hydrogen potential.
[0048] Examples of the conductive assistant include carbon black, such as graphite, acetylene black, and ketjen black, and carbon fiber. The content of the conductive assistant is preferably 20 parts by mass or less, and more preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of the negative electrode active material.
[0049] Examples of the binder include carboxymethyl cellulose, PVDF, PTFE, polyacrylic acid, and fluororubber. Also included are diene rubbers such as styrene-butadiene rubber. The content of the binder is preferably 10 parts by mass or less, more preferably 0.5 to 6 parts by mass, based on 100 parts by mass of the negative electrode active material.
[0050] The negative electrode active material layer is formed by dispersing a negative electrode mixture, which is a mixture of a negative electrode active material and, if necessary, a conductive assistant and a binder, in a solvent to form a negative electrode mixture-containing slurry, applying the slurry to a negative electrode current collector, drying (solvent removal), and pressing if necessary. There is no particular restriction on such a solvent, and a conventionally known solvent can be used. Examples of the solvent include N-methyl-2-pyrrolidone, dimethylformamide, dimethylacetamide, and water.
[0051] The negative electrode current collector is made of a metal foil such as copper foil, nickel foil, or stainless steel foil. The surface of the negative electrode current collector may be carbon-coated, or the negative electrode current collector may be processed into a mesh shape. The thickness of the negative electrode current collector is preferably 5 to 40 μm, more preferably 6 to 35 μm, and even more preferably 7 to 30 μm. In the case of a mesh-shaped negative electrode current collector, the thickness may be measured at a non-porous portion.
[0052] <Non-aqueous electrolyte> In this specification, the term "nonaqueous electrolyte" (hereinafter simply referred to as "electrolyte") refers to an electrolyte containing 1 mass % or less of water relative to the total amount of the electrolyte.
[0053] The electrolyte according to the present embodiment is preferably free of water as much as possible, but may contain a very small amount of water as long as it does not impede the solution of the problem of the present invention. The content of such water is 300 mass ppm or less, more preferably 200 mass ppm or less, based on the total amount of the nonaqueous electrolyte. As long as the nonaqueous electrolyte has a configuration for achieving the solution of the problem of the present invention, the other components can be appropriately selected and applied from the constituent materials in the known nonaqueous electrolyte used in lithium ion batteries.
[0054] In this embodiment, the non-aqueous electrolyte contains acetonitrile as a non-aqueous solvent and lithium bisfluorosulfonylimide, i.e., LiN(SOF), as a lithium salt. 2、 and LiPF6 and the following general formula (I) as an additive for protecting an electrode: [ka] In the formula, R1 and R2 are each an alkyl group having 1 to 4 carbon atoms in which a hydrogen atom may be substituted with a fluorine atom, or R1 and R2 may be bonded to form a ring. and a sulfite ester compound represented by the formula:
[0055] <Non-aqueous solvent> Here, the non-aqueous solvent will be described. In the present embodiment, the "non-aqueous solvent" refers to the elements in the electrolyte excluding the lithium salt and various additives. When the electrolyte contains an additive for protecting an electrode, the "non-aqueous solvent" refers to the elements in the electrolyte excluding additives other than the lithium salt and the additive for protecting an electrode. Examples of the non-aqueous solvent include alcohols such as methanol and ethanol; aprotic solvents, etc. Among them, aprotic solvents are preferred. As long as the effect of the present invention is not impaired, the non-aqueous solvent may contain a solvent other than the aprotic solvent.
[0056] Specific examples of aprotic solvents include cyclic carbonates. Examples of cyclic carbonates include carbonates such as ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, trans-2,3-butylene carbonate, cis-2,3-butylene carbonate, 1,2-pentylene carbonate, trans-2,3-pentylene carbonate, cis-2,3-pentylene carbonate, vinylene carbonate, 4,5-dimethylvinylene carbonate, and vinylethylene carbonate; 4-fluoro-1,3-dioxolan-2-one, 4,4-difluoro-1,3-dioxolan-2-one. fluorinated cyclic carbonates represented by cis-4,5-difluoro-1,3-dioxolan-2-one, trans-4,5-difluoro-1,3-dioxolan-2-one, 4,4,5-trifluoro-1,3-dioxolan-2-one, 4,4,5,5-tetrafluoro-1,3-dioxolan-2-one, and 4,4,5-trifluoro-5-methyl-1,3-dioxolan-2-one; lactones represented by γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ-caprolactone, and ε-caprolactone.
[0057] Specific examples of aprotic solvents include sulfur compounds such as ethylene sulfite, propylene sulfite, butylene sulfite, pentene sulfite, sulfolane, 3-sulfolene, 3-methyl sulfolane, 1,3-propane sultone, 1,4-butane sultone, 1-propene 1,3-sultone, dimethyl sulfoxide, tetramethylene sulfoxide, and ethylene glycol sulfite; and cyclic ethers such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, and 1,3-dioxane.
[0058] Specific examples of the aprotic solvent include chain carbonates, such as chain carbonates typified by ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, methyl butyl carbonate, dibutyl carbonate, and ethyl propyl carbonate; and chain fluorinated carbonates typified by trifluorodimethyl carbonate, trifluorodiethyl carbonate, and trifluoroethyl methyl carbonate.
[0059] Specific examples of aprotic solvents include mononitriles such as acetonitrile, propionitrile, butyronitrile, valeronitrile, benzonitrile, and acrylonitrile; alkoxy-substituted nitriles such as methoxyacetonitrile and 3-methoxypropionitrile; dinitriles such as malononitrile, succinonitrile, glutaronitrile, adiponitrile, 1,4-dicyanoheptane, 1,5-dicyanopentane, 1,6-dicyanoheptane, 1,7-dicyanoheptane, 2,6-dicyanoheptane, 1,8-dicyanooctane, 2,7-dicyanooctane, 1,9-dicyanononane, 2,8-dicyanononane, 1,10-dicyanodecane, 1,6-dicyanodecane, and 2,4-dimethylglutaronitrile; and cyclic nitriles such as benzonitrile.Methyl acetate, methyl propionate, methyl isobutyrate, methyl butyrate, methyl isovalerate, methyl valerate, methyl pivalate, methyl hydroangelate, methyl caproate, ethyl acetate, ethyl propionate, ethyl isobutyrate, ethyl butyrate, ethyl isovalerate, ethyl valerate, ethyl pivalate, ethyl hydroangelate, ethyl caproate, propyl acetate, propyl propionate, propyl isobutyrate, propyl butyrate, propyl isovalerate, propyl valerate, propyl pivalate, propyl hydroangelate, propyl caproate, isopropyl acetate, isopropyl propionate, isopropyl isobutyrate, isopropyl butyrate, isopropyl isovalerate, isopropyl valerate, isopropyl pivalate, isopropyl hydroangelate, isopropyl caproate, butyl acetate, butyl propionate, Chain esters such as butyl isobutyrate, butyl butyrate, butyl isovalerate, butyl valerate, butyl pivalate, butyl hydroangelate, butyl caproate, isobutyl acetate, isobutyl propionate, isobutyl isobutyrate, isobutyl butyrate, isobutyl isovalerate, isobutyl valerate, isobutyl pivalate, isobutyl hydroangelate, isobutyl caproate, tert-butyl acetate, tert-butyl propionate, tert-butyl isobutyrate, tert-butyl butyrate, tert-butyl isovalerate, tert-butyl valerate, tert-butyl pivalate, tert-butyl hydroangelate, and tert-butyl caproate; chain ethers such as dimethoxyethane, diethyl ether, 1,3-dioxolane, diglyme, triglyme, and tetraglyme; Rf; A -OR B (In the formula, Rf A represents an alkyl group containing a fluorine atom, and R B represents an organic group which may contain a fluorine atom); and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.
[0060] Furthermore, examples of the compound in which some or all of the H atoms of the aprotic solvent are substituted with halogen atoms include compounds in which the halogen atoms are fluorine; Examples include:
[0061] Here, examples of fluorinated chain carbonates include methyl trifluoroethyl carbonate, trifluorodimethyl carbonate, trifluorodiethyl carbonate, trifluoroethylmethyl carbonate, methyl 2,2-difluoroethyl carbonate, methyl 2,2,2-trifluoroethyl carbonate, and methyl 2,2,3,3-tetrafluoropropyl carbonate. The above-mentioned fluorinated chain carbonates are represented by the following general formula: R c -OC(O)OR d {where, R c and R d is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and CH2Rf e Rf is at least one selected from the group consisting of e is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted with at least one fluorine atom, and R c and / or R d contains at least one fluorine atom} It can be expressed as:
[0062] Examples of fluorinated short-chain fatty acid esters include fluorinated short-chain fatty acid esters such as 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, and 2,2,3,3-tetrafluoropropyl acetate. Fluorinated short-chain fatty acid esters are represented by the following general formula: R f -C(O)OR g {where, R f is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, CF3CF2H, CFH2, CF2Rf h , CFHRf h , and CH2Rf i and R g is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and CH2Rf iRf is at least one selected from the group consisting of h is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom may be substituted with at least one fluorine atom, and Rf i is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted with at least one fluorine atom, and R f and / or R g contains at least one fluorine atom, and R f If is CF2H, R g is not CH3} It can be expressed as:
[0063] These are used alone or in combination of two or more. Among these non-aqueous solvents, it is more preferable to use one or more of cyclic carbonates and chain carbonates from the viewpoint of improving stability. Here, only one of the cyclic carbonates and chain carbonates exemplified above may be selected and used, or two or more (for example, two or more of the cyclic carbonates exemplified above, two or more of the chain carbonates exemplified above, or two or more of the cyclic carbonates exemplified above and one or more of the chain carbonates exemplified above) may be used. Among these, ethylene carbonate, propylene carbonate, vinylene carbonate, or fluoroethylene carbonate is more preferable as the cyclic carbonate, and ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate is more preferable as the chain carbonate. And, since the degree of ionization of the lithium salt that contributes to the charge and discharge of the non-aqueous secondary battery is increased, it is even more preferable to use a cyclic carbonate. When a cyclic carbonate is used, it is particularly preferred that such cyclic carbonate comprises at least one of vinylene carbonate or fluoroethylene carbonate.
[0064] By containing acetonitrile in the non-aqueous solvent of the non-aqueous electrolyte, the ionic conductivity of the non-aqueous electrolyte is improved, and the diffusibility of lithium ions in the battery can be increased. Therefore, when the electrolyte contains acetonitrile, even in a positive electrode in which the positive electrode active material layer is thickened to increase the amount of positive electrode active material filled, lithium ions can be well diffused to the area near the current collector where lithium ions are difficult to reach during high-load discharge. Therefore, it is possible to extract sufficient capacity even during high-load discharge, and a non-aqueous secondary battery with excellent load characteristics can be obtained.
[0065] Furthermore, the nonaqueous solvent of the nonaqueous electrolyte contains acetonitrile, which can improve the rapid charging characteristics of the nonaqueous secondary battery. In constant current (CC)-constant voltage (CV) charging of a nonaqueous secondary battery, the capacity per unit time during the CC charging period is greater than the charge capacity per unit time during the CV charging period. When acetonitrile is used as the nonaqueous solvent of the nonaqueous electrolyte, the range in which CC charging is possible can be expanded (CC charging time can be extended), and the charging current can also be increased, so that the time from the start of charging to fully charging the nonaqueous secondary battery can be significantly shortened.
[0066] On the other hand, acetonitrile is easily electrochemically decomposed by reduction, and therefore, when acetonitrile is used, it is preferable to perform at least one of mixing the acetonitrile with another solvent and adding an additive for protecting an electrode for forming a protective film on the electrode.
[0067] The content of acetonitrile is preferably 5 to 95% by volume based on the total amount of the non-aqueous solvent. The content of acetonitrile is more preferably 10% by volume or more, or 20% by volume or more, or 30% by volume or more, and even more preferably 35% by volume or more, based on the total amount of the non-aqueous solvent. This value is more preferably 85% by volume or less, and even more preferably 66% by volume or less. When the content of acetonitrile is 5% by volume or more based on the total amount of the non-aqueous solvent, the ion conductivity tends to increase and high output characteristics can be expressed, and further, the dissolution of the lithium salt can be promoted. Since the additive described later suppresses the increase in the internal resistance of the battery, when the content of acetonitrile in the non-aqueous solvent is within the above-mentioned range, the high temperature cycle characteristics and other battery characteristics tend to be further improved while maintaining the excellent performance of acetonitrile.
[0068] <Lithium salt> In this embodiment, the non-aqueous electrolyte contains LiN(SO2F)2 and LiPF6 as lithium salts. LiN(SO2F)2 is a lithium salt included in imide salts. In this specification, imide salts are lithium salts represented by the general formula LiN(SO2C m F 2m+1 )2 {wherein m is an integer of 0 to 8}, and specifically includes LiN(SO2CF3)2 in addition to LiN(SO2F)2. The non-aqueous electrolyte may contain an imide salt other than these imide salts.
[0069] Since the saturation concentration of the imide salt in acetonitrile is higher than that of LiPF6, it is preferable to include the imide salt at a molar concentration of LiPF6≦imide salt, since this can suppress association and precipitation of the lithium salt and acetonitrile at low temperatures. In addition, it is preferable that the content of the imide salt is 0.5 mol to 3 mol per 1 L of the non-aqueous solvent from the viewpoint of the amount of ions supplied. Preferably, LiN(SO2F)2 is contained at 1.0 mol or more per 1 L of the non-aqueous electrolyte, and LiPF6 is contained at 0.01 mol or more per 1 L of the non-aqueous electrolyte. The upper limit of the content of LiN(SO2F)2 is 2.5 mol or less per 1 L of the non-aqueous electrolyte, and the upper limit of the content of LiPF6 is 1.0 mol or less per 1 L of the non-aqueous electrolyte. By further including LiN(SO2F)2 and LiPF6 in the above quantitative relationship in addition to acetonitrile, the reduction in ion conductivity in a low temperature range such as −10° C. or −30° C. can be effectively suppressed, and excellent low-temperature characteristics can be obtained. By limiting the content in this manner, it is possible to more effectively suppress the increase in resistance during high-temperature heating.
[0070] The lithium salt may include fluorine-containing inorganic lithium salts other than LiPF, such as LiBF, LiAsF, LiSiF, LiSbF, LiBF, LiAs ... 12 F b H 12-b(wherein b is an integer of 0 to 3) and the like may be included. "Inorganic lithium salt" refers to a lithium salt that does not contain a carbon atom in the anion and is soluble in acetonitrile. "Fluorine-containing inorganic lithium salt" refers to a lithium salt that does not contain a carbon atom in the anion, contains a fluorine atom in the anion, and is soluble in acetonitrile. Fluorine-containing inorganic lithium salts are excellent in that they form a passive film on the surface of the metal foil that is the positive electrode current collector, and inhibit the corrosion of the positive electrode current collector. These fluorine-containing inorganic lithium salts are used alone or in combination of two or more. As the fluorine-containing inorganic lithium salt, a compound that is a double salt of LiF and a Lewis acid is desirable, and among them, it is more preferable to use a fluorine-containing inorganic lithium salt having a phosphorus atom, since it is easy to release free fluorine atoms. A typical fluorine-containing inorganic lithium salt is LiPF6, which dissolves and releases PF6 anions. When a fluorine-containing inorganic lithium salt having a boron atom is used as the fluorine-containing inorganic lithium salt, it is preferable because it is easy to capture excess free acid components that may cause battery deterioration, and from this viewpoint, LiBF4 is particularly preferable.
[0071] The content of the fluorine-containing inorganic lithium salt in the non-aqueous electrolyte of this embodiment is not particularly limited, but is preferably 0.01 mol or more per 1 L of non-aqueous solvent, more preferably 0.1 mol or more, and even more preferably 0.25 mol or more. When the content of the fluorine-containing inorganic lithium salt is within the above-mentioned range, the ion conductivity increases and high output characteristics tend to be exhibited. In addition, it is preferably less than 2.8 mol per 1 L of non-aqueous solvent, more preferably less than 1.5 mol, and even more preferably less than 1 mol. When the content of the fluorine-containing inorganic lithium salt is within the above-mentioned range, the ion conductivity increases and high output characteristics can be exhibited, and the decrease in ion conductivity associated with the increase in viscosity at low temperatures tends to be suppressed, and the high temperature cycle characteristics and other battery characteristics tend to be further improved while maintaining the excellent performance of the non-aqueous electrolyte.
[0072] The nonaqueous electrolyte solution of the present embodiment may further contain an organic lithium salt. The term "organic lithium salt" refers to a lithium salt that contains a carbon atom in the anion and is soluble in acetonitrile.
[0073] The organic lithium salt may be an organic lithium salt having an oxalic acid group. Specific examples of the organic lithium salt having an oxalic acid group include organic lithium salts represented by LiB(C2O4)2, LiBF2(C2O4), LiPF4(C2O4), and LiPF2(C2O4)2, and among them, at least one lithium salt selected from the lithium salts represented by LiB(C2O4)2 and LiBF2(C2O4) is preferred. It is more preferred to use one or more of these together with a fluorine-containing inorganic lithium salt. The organic lithium salt having an oxalic acid group may be added to a non-aqueous electrolyte solution or may be contained in the negative electrode (negative electrode active material layer).
[0074] The amount of the organic lithium salt having an oxalic acid group added to the non-aqueous electrolyte is preferably 0.005 mol or more, more preferably 0.02 mol or more, and even more preferably 0.05 mol or more per 1L of the non-aqueous solvent of the non-aqueous electrolyte, from the viewpoint of better ensuring the effect of its use. However, if the amount of the organic lithium salt having an oxalic acid group in the non-aqueous electrolyte is too large, there is a risk of precipitation. Therefore, the amount of the organic lithium salt having an oxalic acid group added to the non-aqueous electrolyte is preferably less than 1.0 mol, more preferably less than 0.5 mol, and even more preferably less than 0.2 mol per 1L of the non-aqueous solvent of the non-aqueous electrolyte.
[0075] It is known that organic lithium salts having oxalic acid groups are poorly soluble in organic solvents with low polarity, particularly in chain carbonates. Organic lithium salts having oxalic acid groups may contain a small amount of lithium oxalate, and may react with a small amount of water contained in other raw materials when mixed to form a non-aqueous electrolyte solution, resulting in the generation of new white precipitation of lithium oxalate. Therefore, the content of lithium oxalate in the non-aqueous electrolyte solution of this embodiment is not particularly limited, but is preferably 0 to 500 ppm.
[0076] In addition to the above, lithium salts generally used for non-aqueous secondary batteries may be added supplementarily as the lithium salt in this embodiment. Specific examples of other lithium salts include LiClO4, LiAlO4, LiAlCl4, LiB 10 Cl 10 Inorganic lithium salts that do not contain fluorine atoms in the anion, such as chloroborane Li; LiCF3SO3, LiCF3CO2, Li2C2F4(SO3)2, LiC(CF3SO2)3, LiC n F (2n+1) SO3 (wherein n ≧ 2), organic lithium salts such as lower aliphatic carboxylic acids, Li tetraphenylborate, and LiB(C3O4H2)2; LiPF such as LiPF5(CF3) n (C p F 2p+1 ) 6-n [wherein n is an integer of 1 to 5, and p is an integer of 1 to 8]; LiBF such as LiBF3(CF3) q (C s F 2s+1 ) 4-q [wherein q is an integer of 1 to 3, and s is an integer of 1 to 8]; a lithium salt bonded to a polyvalent anion; LiC(SO2R A )(SO2R B )(SO2R C ) (a) {where, R A , R B , and R Cmay be the same or different and represent a perfluoroalkyl group having 1 to 8 carbon atoms. The following formula (b): LiN(SO2OR D )(SO2OR E ) (b) {where, R D , and R E may be the same or different and represent a perfluoroalkyl group having 1 to 8 carbon atoms.}, and The following formula (c): LiN(SO2R F )(SO2OR G ) (c) {where, R F , and R G may be the same or different and represent a perfluoroalkyl group having 1 to 8 carbon atoms.} One or more of these can be used together with the fluorine-containing inorganic lithium salt.
[0077] <Sulfite ester compounds> In this embodiment, the nonaqueous electrolyte solution is a compound represented by the following general formula (I): [ka] {In the formula, R1 and R2 are an alkyl group having 1 to 4 carbon atoms in which a hydrogen atom may be substituted with a fluorine atom, or R1 and R2 may be bonded to form a ring} The sulfite ester compound includes a sulfite ester compound represented by the formula:
[0078] In general formula (I), R1 and R2 may each independently be an unsubstituted alkyl group having 1 to 4 carbon atoms, or a fluoroalkyl group having 1 to 4 carbon atoms in which some or all of the hydrogen atoms have been substituted with fluorine atoms. When R1 and R2 are bonded to form a cyclic sulfite ester compound, the linkage between R1 and R2 may have 2 to 8 carbon atoms.
[0079] Specific examples of sulfite compounds include dimethyl sulfite, diethyl sulfite, dipropyl sulfite, dibutyl sulfite, diisopropyl sulfite, di(2-butyl) sulfite, ethylene sulfite, 1,2-propylene sulfite, 1,3-propylene sulfite, methyl-1,3-propylene sulfite, butylene sulfite, etc. Among these, ethylene sulfite is preferred from the viewpoint of forming a protective coating having a high electrode protection effect.
[0080] The content of the sulfite ester compound is preferably 1% by volume or more and 5% by volume or less, more preferably 2% by volume or more and 4% by volume or less, based on the total amount of the non-aqueous solvent. When the content of the sulfite ester compound is 1% by volume or more, based on the total amount of the non-aqueous solvent, an electrode protection effect tends to be obtained. Also, when the sulfite ester compound is contained in an amount of 5% or less, based on the total amount of the non-aqueous solvent, inhibition of the electrode reaction tends to be suppressed.
[0081] <Additives for electrode protection> The electrolyte solution in this embodiment may also contain additives that protect other electrodes. There are no particular limitations on the additives for protecting the electrodes as long as they do not impede the problem-solving of the present invention. The additives may substantially overlap with the substance that plays the role of a solvent for dissolving lithium salts (i.e., the above-mentioned non-aqueous solvent). The additives for protecting the electrodes are preferably substances that contribute to improving the performance of the electrolyte solution and the non-aqueous secondary battery in this embodiment, but also include substances that are not directly involved in electrochemical reactions.
[0082] Specific examples of the electrode protection additive include 4-fluoro-1,3-dioxolane-2-one, 4,4-difluoro-1,3-dioxolane-2-one, cis-4,5-difluoro-1,3-dioxolane-2-one, trans-4,5-difluoro-1,3-dioxolane-2-one, 4,4,5-trifluoro-1,3-dioxolane-2-one, 4,4,5,5-tetrafluoro-1,3 -dioxolane-2-one, and fluoroethylene carbonates such as 4,4,5-trifluoro-5-methyl-1,3-dioxolane-2-one; unsaturated bond-containing cyclic carbonates such as vinylene carbonate, 4,5-dimethylvinylene carbonate, and vinylethylene carbonate; γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ- Examples of the acid anhydride include lactones such as caprolactone and ε-caprolactone, cyclic ethers such as 1,4-dioxane, cyclic sulfur compounds such as sulfolane, 3-sulfolene, 3-methylsulfolane, 1,3-propane sultone, 1,4-butane sultone, 1-propene 1,3-sultone, and tetramethylene sulfoxide, chain acid anhydrides such as acetic anhydride, propionic anhydride, and benzoic anhydride, cyclic acid anhydrides such as malonic anhydride, succinic anhydride, glutaric anhydride, maleic anhydride, phthalic anhydride, 1,2-cyclohexanedicarboxylic anhydride, 2,3-naphthalene dicarboxylic anhydride, and naphthalene-1,4,5,8-tetracarboxylic dianhydride, and mixed acid anhydrides having a structure in which different types of acids, such as two different types of carboxylic acids or a carboxylic acid and a sulfonic acid, are dehydrated and condensed. These may be used alone or in combination of two or more types.
[0083] The content of the electrode protection additive in the electrolyte solution in this embodiment is not particularly limited, but the content of the electrode protection additive relative to the total amount of the non-aqueous solvent is preferably 0.1 to 30 volume %, more preferably 0.3 to 15 volume %, and even more preferably 0.5 to 4 volume %.
[0084] In this embodiment, the greater the content of the electrode protection additive, the more the deterioration of the electrolyte solution is suppressed. However, the smaller the content of the electrode protection additive, the more the high-output characteristics of the non-aqueous secondary battery in a low-temperature environment are improved. Therefore, by adjusting the content of the electrode protection additive within the above-mentioned range, it is likely that the excellent performance based on the high ionic conductivity of the electrolyte solution can be maximized without impairing the basic function of the non-aqueous secondary battery. By preparing the electrolyte solution with such a composition, it is likely that the cycle performance of the non-aqueous secondary battery, the high-output performance in a low-temperature environment, and all other battery characteristics can be further improved.
[0085] In addition, since acetonitrile, which is one component of the non-aqueous solvent, is easily reductively decomposed electrochemically, the non-aqueous solvent containing acetonitrile preferably contains one or more cyclic aprotic polar solvents as an electrode protection additive for forming a protective coating on the negative electrode, and more preferably contains one or more unsaturated bond-containing cyclic carbonates.
[0086] As the unsaturated bond-containing cyclic carbonate, vinylene carbonate is preferred, and the content of vinylene carbonate in the non-aqueous electrolyte is preferably 0.1% by volume or more and 4% by volume or less, more preferably 0.2% by volume or more and less than 3% by volume, and even more preferably 0.5% by volume or more and less than 2.5% by volume. This makes it possible to more effectively improve low-temperature durability and provide a secondary battery with excellent low-temperature performance.
[0087] Vinylene carbonate is often essential as an additive for electrode protection because it suppresses the reductive decomposition reaction of acetonitrile on the surface of the negative electrode, and if it is insufficient, battery performance may rapidly decrease. On the other hand, excessive film formation leads to a decrease in low-temperature performance. Therefore, by adjusting the amount of vinylene carbonate added within the above range, it is possible to keep the interface (film) resistance low and suppress cycle deterioration at low temperatures.
[0088] <Other optional additives> In this embodiment, for the purpose of improving the charge / discharge cycle characteristics, high-temperature storage properties, and safety (e.g., prevention of overcharging) of the nonaqueous secondary battery, an optional additive selected from sulfonic acid esters, diphenyl disulfide, cyclohexylbenzene, biphenyl, fluorobenzene, tert-butylbenzene, phosphate esters [ethyl diethyl phosphonoacetate (EDPA): (C2H5O)2(P=O)-CH2(C=O)OC2H5, tris(trifluoroethyl) phosphate (TFEP): (CF3CHO)3P=O, triphenyl phosphate (TPP): (C6H5O)3P=O: (CH2=CHCHO)3P=O, triallyl phosphate, etc.], nitrogen-containing cyclic compounds with no steric hindrance around the unshared electron pair [pyridine, 1-methyl-1H-benzotriazole, 1-methylpyrazole, etc.], and derivatives of these compounds can also be appropriately added to the nonaqueous electrolyte. In particular, phosphoric acid esters are effective in suppressing side reactions during storage.
[0089] The content of other optional additives in this embodiment is calculated as a mass percentage relative to the total mass of all components constituting the non-aqueous electrolyte. There is no particular limitation on the content of other optional additives, but it is preferably in the range of 0.01 mass% to 10 mass%, more preferably 0.02 mass% to 5 mass%, and even more preferably 0.05 to 3 mass% relative to the total amount of the non-aqueous electrolyte. By adjusting the content of other optional additives within the above range, there is a tendency that even better battery characteristics can be added without impairing the basic function as a non-aqueous secondary battery.
[0090] <SO4 2- Content adjustment process> When using commercially available sulfite ester compounds, SO4 2- The non-aqueous electrolyte of the present invention contains a certain amount of SO4 2-By adjusting the concentration (content) of SO4 to a specific range, the battery output characteristics are maintained while suppressing the deterioration of battery characteristics in a high-temperature environment. The cause of this effect has not been fully elucidated, but it is thought that SO4 2- It is presumed that when a substance containing such ions is included in the electrolyte within a specific concentration range, a coating that suppresses the decomposition of acetonitrile even at high temperatures, such as around 85°C, is formed at the negative electrode interface, thereby improving high-temperature stability.
[0091] In non-aqueous electrolytes, SO4 2- If the content is too low, the film formation effect is insufficient, and if the content is too high, the interface (film) resistance increases, resulting in a decrease in output performance. 2- The content of is in the range of 10 ppm or more and 500 ppm or less, and preferably in the range of 20 ppm or more and 350 ppm or less, relative to the nonaqueous electrolyte solution.
[0092] SO4 in the present invention 2- As a method for adjusting the content of SO4, for example, after dissolving a sulfite ester compound in a non-aqueous solvent, molecular sieves are added to the mixed solution and left for a certain period of time. 2- Then, the SO4 in the mixed solution can be reduced. 2- The content of is checked, and is maintained as long as it is within the concentration range described above. If it is too much, the contact time with the molecular sieve is extended, and if it is too little, it can be adjusted by adding a required amount of salt containing the missing anion to the non-aqueous electrolyte. Lithium is preferable as the cation of the salt used in this case. The molecular sieve may be a commercially available one or may be synthesized. After adding the molecular sieve to the mixed solution, it may be heated or stirred as appropriate.
[0093] <separator> In the present embodiment, the nonaqueous secondary battery 100 is preferably provided with a separator 170 between the positive electrode 150 and the negative electrode 160 from the viewpoint of preventing short circuits between the positive electrode 150 and the negative electrode 160 and providing safety such as shutdown. The separator 170 is not limited, but may be the same as that provided in known nonaqueous secondary batteries, and is preferably an insulating thin film having high ion permeability and excellent mechanical strength. Examples of the separator 170 include woven fabric, nonwoven fabric, and synthetic resin microporous membrane, and among these, synthetic resin microporous membrane is preferable.
[0094] As the synthetic resin microporous film, for example, a microporous film containing polyethylene or polypropylene as a main component, or a polyolefin-based microporous film such as a microporous film containing both of these polyolefins is preferably used. As the nonwoven fabric, for example, a porous film made of a heat-resistant resin such as glass, ceramic, polyolefin, polyester, polyamide, liquid crystal polyester, or aramid can be used.
[0095] Separator 170 may be configured as a single layer or multiple layers of one type of microporous film, or may be configured as a stack of two or more types of microporous films. Separator 170 may be configured as a single layer or multiple layers of a mixed resin material obtained by melting and kneading two or more types of resin materials.
[0096] For the purpose of providing functions, inorganic particles may be present on the surface or inside of the separator, or other organic layers may be further coated or laminated. The separator may also include a crosslinked structure. In order to improve the safety performance of the nonaqueous secondary battery, these techniques may be combined as necessary.
[0097] By using such a separator 170, it is possible to realize good input / output characteristics and low self-discharge characteristics required for lithium ion secondary batteries for high-power applications. The thickness of the microporous membrane used as the separator is not particularly limited, but is preferably 1 μm or more from the viewpoint of membrane strength, and is preferably 500 μm or less from the viewpoint of permeability. From the viewpoint of use in high-power applications such as safety tests in which the amount of heat generated is relatively high and self-discharge characteristics higher than conventional ones are required, and from the viewpoint of winding properties in a large battery winding machine, the thickness of the separator is preferably 5 μm or more and 30 μm or less, and more preferably 10 μm or more and 25 μm or less. In addition, when attaching importance to both short-circuit resistance and output performance, the thickness of the separator is more preferably 15 μm or more and 25 μm or less, but when attaching importance to both high energy density and output performance, it is more preferably 10 μm or more and less than 15 μm. The porosity of the separator is preferably 30% to 90%, more preferably 35% to 80%, and even more preferably 40% to 70%, from the viewpoint of following the rapid movement of lithium ions during high output. If priority is given to improving output performance while ensuring safety, the porosity of the separator is particularly preferably 50% to 70%, and if emphasis is placed on achieving both short-circuit resistance and output performance, the porosity is particularly preferably 40% to less than 50%. The air permeability of the separator is 1 second / 100 cm from the viewpoint of the balance between the film thickness and the porosity. 3 More than 400 seconds / 100cm 3 Less than 100 seconds / 100 cm is preferable. 3 More than 350 / 100cm 3 In addition, when it is important to achieve both short circuit resistance and output performance, the air permeability of the separator is preferably 150 sec / 100 cm 3 More than 350 seconds / 100cm 3 The following is particularly preferable. If you prioritize improving output performance while ensuring safety, 100 / 100cm 3 150 seconds / 100cm 3is particularly preferably less than 10 mS / cm. On the other hand, when a non-aqueous electrolyte with low ionic conductivity is combined with a separator within the above range, the lithium ion migration rate is not determined by the structure of the separator, but by the high ionic conductivity of the electrolyte, and the expected input / output characteristics tend not to be obtained. Therefore, the ionic conductivity of the non-aqueous electrolyte is preferably 10 mS / cm or more, more preferably 15 mS / cm or more, and even more preferably 20 mS / cm or more. However, the membrane thickness, air permeability and porosity of the separator, and the ionic conductivity of the non-aqueous electrolyte are not limited to the above examples.
[0098] <Battery exterior> The configuration of the battery exterior 110 of the nonaqueous secondary battery 100 in this embodiment is not particularly limited, and for example, any of the battery exteriors of a battery can and a laminate film exterior body can be used. As the battery can, for example, a metal can such as a square, rectangular tube, cylindrical, elliptical, flat, coin, or button type made of steel, stainless steel, aluminum, clad material, etc. can be used. As the laminate film exterior body, for example, a laminate film made of a three-layer structure of a heat-melting resin / metal film / resin can be used.
[0099] The laminate film exterior body can be used as an exterior body by stacking two sheets with the heat-melting resin side facing inward, or by folding the laminate film exterior body so that the heat-melting resin side faces inward, and sealing the ends by heat sealing. When using a laminate film exterior body, the positive electrode lead body 130 (or a lead tab connected to the positive electrode terminal and the positive electrode terminal) may be connected to the positive electrode current collector, and the negative electrode lead body 140 (or a lead tab connected to the negative electrode terminal and the negative electrode terminal) may be connected to the negative electrode current collector. In this case, the laminate film exterior body may be sealed with the ends of the positive electrode lead body 130 and the negative electrode lead body 140 (or the lead tabs connected to the positive electrode terminal and the negative electrode terminal, respectively) pulled out to the outside of the exterior body.
[0100] <Shape of non-aqueous secondary battery> The shape of the nonaqueous secondary battery of this embodiment is not particularly limited, and may be, for example, a cylindrical shape, an elliptical shape, a rectangular tube shape, a button shape, a coin shape, a flat shape, a laminate shape, or the like.
[0101] <Method of manufacturing non-aqueous secondary battery> The nonaqueous secondary battery 100 in this embodiment is produced by a known method using the above-mentioned nonaqueous electrolyte, a positive electrode 150 having a positive electrode active material layer on one or both sides of a current collector, a negative electrode 160 having a negative electrode active material layer on one or both sides of a current collector, a battery exterior 110, and, if necessary, a separator 170.
[0102] First, a laminate is formed consisting of the positive electrode 150, the negative electrode 160, and, if necessary, the separator 170. For example, possible modes include a mode in which the long positive electrode 150 and the negative electrode 160 are wound in a stacked state with the long separator interposed between the positive electrode 150 and the negative electrode 160 to form a laminate with a wound structure; a mode in which the positive electrode sheets and the negative electrode sheets obtained by cutting the positive electrode 150 and the negative electrode 160 into a plurality of sheets having a certain area and shape are alternately stacked with a separator sheet between to form a laminate with a laminate structure; a mode in which a long separator is folded zigzag and a positive electrode body sheet and a negative electrode body sheet are alternately inserted between the zigzag folded separators to form a laminate with a laminate structure; and the like.
[0103] Next, the above-mentioned laminate is housed in a battery exterior 110 (battery case), the electrolyte solution according to this embodiment is poured into the battery case, and the laminate is immersed in the electrolyte solution and sealed, thereby producing the nonaqueous secondary battery according to this embodiment.
[0104] In another embodiment, a gel-state electrolyte membrane is prepared in advance by impregnating a substrate made of a polymer material with an electrolytic solution, and a laminate structure is formed using sheet-like positive electrode 150, negative electrode 160, and electrolyte membrane, and, if necessary, separator 170, and then the laminate is housed in battery exterior 110 to prepare nonaqueous secondary battery 100.
[0105] In addition, if the arrangement of the electrodes is designed so that there is a portion where the outer peripheral edge of the negative electrode active material layer overlaps with the outer peripheral edge of the positive electrode active material layer, or there is a portion where the width is too small in the non-facing portion of the negative electrode active material layer, the position of the electrodes may be shifted during battery assembly, which may deteriorate the charge-discharge cycle characteristics of the non-aqueous secondary battery. Therefore, it is preferable that the electrode positions of the electrode body used in the non-aqueous secondary battery are fixed in advance by tapes such as polyimide tape, polyphenylene sulfide tape, and polypropylene (PP) tape, adhesives, etc.
[0106] In this embodiment, when a non-aqueous electrolyte using acetonitrile is used, the lithium ions released from the positive electrode during the initial charge of the non-aqueous secondary battery may diffuse throughout the negative electrode due to its high ionic conductivity. In non-aqueous secondary batteries, the area of the negative electrode active material layer is generally made larger than that of the positive electrode active material layer. However, if lithium ions diffuse and are absorbed to a portion of the negative electrode active material layer that does not face the positive electrode active material layer, the lithium ions will not be released during the initial discharge and will remain in the negative electrode. Therefore, the contribution of the lithium ions that are not released becomes irreversible capacity. For these reasons, the initial charge / discharge efficiency may be low in non-aqueous secondary batteries using a non-aqueous electrolyte containing acetonitrile.
[0107] On the other hand, if the area of the positive electrode active material layer is larger than that of the negative electrode active material layer or they are the same, current concentration is likely to occur at the edge portions of the negative electrode active material layer during charging, making it easier for lithium dendrites to form.
[0108] The ratio of the area of the entire negative electrode active material layer to the area of the portion where the positive electrode active material layer and the negative electrode active material layer face each other is not particularly limited, but for the reasons described above, it is preferably greater than 1.0 and less than 1.1, more preferably greater than 1.002 and less than 1.09, even more preferably greater than 1.005 and less than 1.08, and particularly preferably greater than 1.01 and less than 1.08. In a nonaqueous secondary battery using a nonaqueous electrolyte solution containing acetonitrile, the initial charge / discharge efficiency can be improved by reducing the ratio of the area of the entire negative electrode active material layer to the area of the portion where the positive electrode active material layer and the negative electrode active material layer face each other.
[0109] Reducing the ratio of the area of the entire negative electrode active material layer to the area of the portion where the positive electrode active material layer and the negative electrode active material layer face each other means limiting the ratio of the area of the portion of the negative electrode active material layer that does not face the positive electrode active material layer. This makes it possible to reduce as much as possible the amount of lithium ions absorbed in the portion of the negative electrode active material layer that does not face the positive electrode active material layer among the lithium ions released from the positive electrode during the initial charge (i.e., the amount of lithium ions that are not released from the negative electrode during the initial discharge and become irreversible capacity). Therefore, by designing the ratio of the area of the entire negative electrode active material layer to the area of the portion where the positive electrode active material layer and the negative electrode active material layer face each other within the above range, it is possible to improve the load characteristics of the battery by using acetonitrile, increase the initial charge / discharge efficiency of the battery, and further suppress the generation of lithium dendrites.
[0110] The non-aqueous secondary battery 100 in this embodiment can function as a battery by initial charging, but is stabilized by decomposing a part of the electrolyte during the initial charging. There is no particular restriction on the method of initial charging, but the initial charging is preferably performed at 0.001 to 0.3C, more preferably at 0.002 to 0.25C, and even more preferably at 0.003 to 0.2C. A preferable result is also obtained when the initial charging is performed via a constant voltage charging in the middle. The constant current for discharging the design capacity in one hour is 1C. By setting the voltage range in which the lithium salt is involved in the electrochemical reaction to be long, a stable and strong SEI is formed on the electrode surface, and there is an effect of suppressing an increase in internal resistance. In addition, the reaction product is not firmly fixed only to the negative electrode 160, but has a good effect on the members other than the negative electrode 160, such as the positive electrode 150 and the separator 170, in some form. For this reason, it is very effective to perform the initial charging in consideration of the electrochemical reaction of the lithium salt dissolved in the non-aqueous electrolyte.
[0111] The nonaqueous secondary battery 100 in this embodiment can also be used as a battery pack in which a plurality of nonaqueous secondary batteries 100 are connected in series or in parallel. From the viewpoint of managing the charge / discharge state of the battery pack, the operating voltage range per battery is preferably 2V to 5V, more preferably 2.5V to 5V, and particularly preferably 2.75V to 5V.
[0112] Although the embodiment of the present invention has been described above, the present invention is not limited to the above-mentioned embodiment. The present invention can be modified in various ways without departing from the gist of the present invention. EXAMPLES
[0113] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0114] (1) Preparation of non-aqueous electrolyte In an inert atmosphere, various non-aqueous solvents, various sulfite ester compounds, and various additives were mixed to a predetermined concentration, and various lithium salts were added to the mixture to a predetermined concentration to prepare non-aqueous electrolyte solutions (S1) to (S6). The compositions of these non-aqueous electrolyte solutions are shown in Table 1.
[0115] The abbreviations for the non-aqueous solvent, lithium salt, sulfite compound, and additives in Table 1 have the following meanings. (Non-aqueous solvent) AcN: Acetonitrile DEC: Diethyl carbonate EC: Ethylene carbonate VC: Vinylene carbonate (Sulfite ester compounds) ES: Ethylene sulfite (Lithium salts) LiPF6: Lithium hexafluorophosphate LiFSI: Lithium bis(fluorosulfonyl)imide (LiN(SO2F)2)
[0116] [Table 1]
[0117] After preparation, the non-aqueous electrolytes S1, S2, S3, S4, and S5 were mixed with 1 g of molecular sieve (5A 1 / 16 manufactured by Kanto Chemical Co., Ltd.) per 10 g of the non-aqueous electrolyte, and left for 24 hours with occasional stirring. 2- The amount of SO4 was measured using ion chromatography. 2- The amount is about 20 ppm, and for S2, SO4 2- The amount was adjusted to about 300 ppm, and S5 was used for battery evaluation without any adjustment.
[0118] In addition, the non-aqueous electrolyte S6 was used for battery evaluation without being treated with a molecular sieve after preparation.
[0119] (2) Preparation of coin-type non-aqueous secondary batteries (2-1) Preparation of positive electrode (A) Lithium iron phosphate (LiFePO4) having an olivine structure as a positive electrode active material, (B) carbon black powder as a conductive additive, and polyvinylidene fluoride (PVDF) as a binder were mixed in a mass ratio of 84:10:6 to obtain a positive electrode mixture.
[0120] N-methyl-2-pyrrolidone was added as a solvent to the obtained positive electrode mixture so that the solid content was 68 mass% and further mixed to prepare a positive electrode mixture-containing slurry. The positive electrode mixture-containing slurry was applied to one side of an aluminum foil having a thickness of 15 μm and a width of 280 mm as a positive electrode current collector, while adjusting the basis weight of the positive electrode mixture-containing slurry, so as to have a coating width of 240 to 250 mm, a coating length of 125 mm, and an uncoated length of 20 mm, using a three-roll transfer coater, and the solvent was dried and removed in a hot air drying furnace. The obtained electrode roll was trimmed on both sides and dried under reduced pressure at 130°C for 8 hours. Thereafter, the density of the positive electrode active material layer was adjusted to 1.9 g / cm by roll pressing. 3 A positive electrode consisting of the positive electrode active material layer and the positive electrode current collector was obtained by rolling the positive electrode active material layer so that the coating weight excluding the positive electrode current collector was 17.5 mg / cm. 2 It was.
[0121] (2-2) Preparation of negative electrode Graphite powder as the negative electrode active material, carbon black powder as the conductive additive, and carboxymethyl cellulose and styrene butadiene rubber as the binder were mixed in a solid mass ratio of 95.7:0.5:binder to 3.8:negative electrode active material:0.5:binder to obtain a negative electrode mixture.
[0122] Water was added as a solvent to the obtained negative electrode mixture so that the solid content was 45 mass% and further mixed to prepare a negative electrode mixture-containing slurry. The negative electrode mixture-containing slurry was applied to one side of a copper foil having a thickness of 8 μm and a width of 280 mm, which serves as a negative electrode current collector, while adjusting the basis weight of the negative electrode mixture-containing slurry, so as to have a coating pattern of 240 to 250 mm in coating width, 125 mm in coating length, and 20 mm in non-coating length, using a three-roll transfer coater, and the solvent was dried and removed in a hot air drying furnace. The obtained electrode roll was trimmed on both sides and dried under reduced pressure at 80°C for 12 hours. Thereafter, the density of the negative electrode active material layer was adjusted to 1.5 g / cm by roll pressing. 3 The negative electrode was obtained by rolling the negative electrode active material layer and the negative electrode current collector so that the coating weight excluding the negative electrode current collector was 7.5 mg / cm. 2 It was.
[0123] (2-3) Assembly of coin-type non-aqueous secondary batteries A polypropylene gasket was set in a CR2032 type battery case (SUS304 / Al clad), and the positive electrode obtained as described above was punched into a disk shape with a diameter of 15.958 mm and set in the center with the positive electrode active material layer facing up. A glass fiber filter paper (GA-100, manufactured by Advantec Co., Ltd.) punched into a disk shape with a diameter of 16.156 mm was set on top of it, and 150 μL of non-aqueous electrolyte was poured, and then the negative electrode obtained as described above was punched into a disk shape with a diameter of 16.156 mm and set with the negative electrode active material layer facing down. After setting the spacer and spring, the battery cap was fitted and crimped with a crimping machine. The overflowing electrolyte was wiped off with a rag. The laminate was kept at 25 ° C for 12 hours, and the non-aqueous electrolyte was thoroughly absorbed into the laminate to obtain a coin-type non-aqueous secondary battery.
[0124] (3) Evaluation of coin-type non-aqueous secondary batteries The coin-type non-aqueous secondary batteries obtained as described above were first subjected to an initial charge process and an initial charge / discharge capacity measurement according to the procedure (3-1) below. Next, each coin-type non-aqueous secondary battery was evaluated according to the procedures (3-2) to (3-3) below. Charging and discharging were performed using a charge / discharge device ACD-M01A (product name) manufactured by Asuka Electronics Co., Ltd. and a programmable thermostatic bath IN804 (product name) manufactured by Yamato Scientific Co., Ltd.
[0125] Here, 1C means the current value at which a fully charged battery is expected to be discharged completely in one hour when discharged at a constant current.
[0126] (3-1) Initial charge / discharge treatment of coin-type non-aqueous secondary batteries The ambient temperature of the coin-type nonaqueous secondary battery was set to 25°C, and it was charged at a constant current of 0.46 mA, which corresponds to 0.1 C, until it reached 3.8 V, and then it was charged at a constant voltage of 3.8 V until the current decayed to 0.05 C. It was then discharged to 2.5 V at a constant current of 1.38 mA, which corresponds to 0.3 C.
[0127] (3-2) -40℃ discharge test The coin-type non-aqueous secondary battery that had been subjected to the initial charge / discharge treatment by the method described in (3-1) above was set at an ambient temperature of 25° C., charged at a constant current of 2.3 mA equivalent to 0.5 C to reach 3.8 V, then charged at a constant voltage of 3.8 V until the current attenuated to 0.05 C, and discharged to 2.5 V at a current value of 0.46 mA equivalent to 0.1 C. After that, charged at a constant current of 2.3 mA equivalent to 0.5 C to reach 3.8 V, then charged at a constant voltage of 3.8 V until the current attenuated to 0.05 C. Next, the ambient temperature of the battery was set to −40° C., and after a waiting time of 3 hours, discharged to 2.5 V at a current value of 0.46 mA equivalent to 0.1 C.
[0128] The discharge capacity at -40°C was calculated as the capacity retention rate when the discharge capacity at 25°C was taken as 100%.
[0129] (3-3) 85℃ storage test The small non-aqueous secondary battery that had been subjected to the initial charge / discharge treatment according to the method described in (3-1) above was charged at a constant current equivalent to 1C at an ambient temperature of 25°C until it reached a fully charged state, and then charged at a constant voltage for 1.5 hours. Next, this coin-type non-aqueous secondary battery was stored in a thermostatic chamber at 85°C for 2 weeks (336 hours). After that, the ambient temperature was returned to 25°C, and the battery was discharged to 2.5V at a current value of 0.46mA equivalent to 0.1C. The remaining discharge capacity at this time was taken as the remaining discharge capacity after 2 weeks. The remaining capacity retention rate was calculated based on the following formula as the measured value of the 85°C 2-week fully charged storage test. Remaining capacity after 2 weeks = (remaining discharge capacity after 2 weeks / initial capacity) x 100 [%]
[0130] [Examples 1 and 2 and Comparative Examples 1 to 4] A coin-type nonaqueous secondary battery was fabricated according to the method described in (2) above using the positive electrode, negative electrode, and nonaqueous electrolyte solution shown in Table 1. Next, each coin-type nonaqueous secondary battery was evaluated according to the procedures described in (3-1) to (3-3) above. The test results are shown in Table 2.
[0131] [Table 2]
[0132] As shown in Table 2, Examples 1 and 2 contain ethylene sulfite and SO4 2- The electrolyte used had undergone a content adjustment process, and showed a capacity retention rate of 56% or more in a discharge test at -40°C and a remaining capacity retention rate of 48% or more in a storage test at 85°C.
[0133] Comparative Example 1 uses an electrolyte solution that does not contain acetonitrile or LiFSI, but the capacity retention rate in the -40°C discharge test is reduced to 20% or less, and therefore it is understood that the Example has excellent low-temperature characteristics. In addition, Comparative Example 1 does not contain a sulfite ester compound and does not contain SO4 2- Although the content adjustment process was carried out, the remaining capacity retention rate in the 85°C storage test also fell to 20% or less.
[0134] On the other hand, Comparative Example 2 contains acetonitrile and LiFSI, but does not contain any sulfite ester compounds and does not contain SO4 2- An electrolyte with an adjusted amount of ions was used, and compared to Comparative Example 1, improved performance was observed in both the -40°C discharge test and the 85°C storage test. However, no improvement in performance was observed in the 85°C storage test, which was only about 37%.
[0135] Comparative Example 3 contains acetonitrile, LiFSI, and a sulfite ester compound, but the amount of SO4 after molecular sieve treatment is 2- When an electrolyte solution without adjusting the amount of ions was used, the performance was equivalent to that of Examples 1 and 2 in the -40°C discharge test, but the discharge rate in the 85°C storage test was about 41%, and high performance was not obtained.
[0136] Comparative Example 4 contains acetonitrile, LiFSI, and a sulfite ester compound, but does not contain SO4 2- When an electrolyte solution without adjusting the amount of ions was used, the performance was equivalent to that of Examples 1 and 2 in the -40°C discharge test, but the performance in the 85°C storage test was only about 45%, which was not as good as that of the Examples.
[0137] The results of this experiment demonstrate that the use of the nonaqueous electrolyte according to the present invention makes it possible to achieve both long-term storage performance in a harsh high-temperature environment of 85°C and battery performance at low temperatures in a nonaqueous secondary battery. [Industrial Applicability]
[0138] The nonaqueous secondary battery of the present invention is expected to be used, for example, as a power source for idling stop systems; rechargeable batteries for automobiles such as hybrid automobiles, plug-in hybrid automobiles, and electric automobiles; low-voltage power sources such as 12 V class power sources, 24 V class power sources, and 48 V class power sources; and residential electricity storage systems. [Explanation of symbols]
[0139] 100 Nonaqueous secondary battery 110 Battery housing 120 Space of battery exterior 110 130 Positive electrode lead body 140 Negative electrode lead body 150 positive electrode 160 negative electrode 170 Separator
Claims
1. A non-aqueous electrolyte solution containing a non-aqueous solvent and a lithium salt, the non-aqueous solvent containing acetonitrile in an amount of 5% by volume or more and 95% by volume or less based on the total amount of the non-aqueous solvent, and the lithium salt containing lithium bisfluorosulfonylimide and LiPF 6 and the following general formula (I): 【Chemistry 1】 {In the formula, R 1 , and R 2 is an alkyl group having 1 to 4 carbon atoms, the hydrogen atom of which may be substituted with a fluorine atom, or R 1 and R 2 may be bonded to form a ring. The nonaqueous electrolyte contains a sulfite compound represented by the formula: 4 2- The non-aqueous electrolyte solution according to claim 1, wherein the content of said component (I) is 10 ppm or more and 500 ppm or less.
2. The nonaqueous electrolyte according to claim 1 , wherein the sulfite ester compound is ethylene sulfite.
3. The non-aqueous electrolyte solution according to claim 1 or 2, wherein the non-aqueous solvent contains a cyclic carbonate.
4. 4. The nonaqueous electrolyte solution according to claim 3, wherein the cyclic carbonate comprises at least one selected from the group consisting of vinylene carbonate and fluoroethylene carbonate.
5. A nonaqueous secondary battery comprising: the nonaqueous electrolyte according to any one of claims 1 to 4; a positive electrode having a positive electrode active material layer on one or both sides of a positive electrode current collector; a negative electrode having a negative electrode active material layer on one or both sides of a negative electrode current collector; and a separator.
6. the positive electrode active material layer contains a lithium-containing metal oxide as a positive electrode active material, The negative electrode active material layer contains lithium ions as a negative electrode active material at 0.4 V vs. Li / Li + 6. The nonaqueous secondary battery according to claim 5, further comprising a material capable of occluding at a potential lower than 0.1V.
Citation Information
Patent Citations
Nonaqueous electrolyte, and lithium battery
JP2010120947A
Nonaqueous electrolytic solution, and nonaqueous secondary battery
JP2015065049A
JPP7366845B
Nonaqueous electrolyte and nonaqueous secondary battery
WO2012057311A1
Non-aqueous secondary battery
WO2013062056A1